Optimizing Energy Consumption by Considering PV Rooftop Generation and Battery Storage in Power Plants: Study Case Palabuhanratu - Dadang Isnandar; Heru Hermawan; Andik Hermawanto (Department of Mechanical and Industrial Engineering, 2026)
The integration of rooftop solar photovoltaic (PV) systems with Battery Energy Storage Systems (BESS) represents a strategic approach to improving energy efficiency and supporting a sustainable energy transition. This study evaluates the operational optimization of a residential-scale PV+BESS system implemented at the safety center building of the Palabuhanratu coal-fired power plant (CFPP) in Indonesia. The research focuses on the influence of battery management strategies—particularly discharge energy savings and battery lifespan, with a detailed analysis of C-rate (current rate index value) and Depth of Discharge (DOD) parameters. Results demonstrate that adjusting discharge timing based on weekday and weekend load profiles can effectively lower C-rate levels from 0.18C to 0.09C and Depth of Discharge from 80% to 73%, potentially extending battery life cycle. Through load-shifting strategies, the optimized operations resulted in energy savings of 3,442.5 kWh and financial benefits of USD 80 between October 2024 and July 2025. These findings highlight the critical role of adaptive energy management in enhancing the technical performance and longevity of residential PV+BESS systems.